The armor of light ebook - Follett, Ken (Kingsbridge, 2023)
The long-awaited sequel to A Column of Fire , The Armor of Light , heralds a new dawn for Kingsbridge, England, where progress clashes with tradition, class struggles push into every part of society, and war in Europe engulfs the entire continent and beyond. The Spinning Jenny was invented in 1770, and with that, a new era of manufacturing and industry changed lives everywhere within a generation. A world filled with unrest wrestles for control over this new world order: A mother’s husband is killed in a work accident due to negligence; a young woman fights to fund her school for impoverished children; a well-intentioned young man unexpectedly inherits a failing business; one man ruthlessly protects his wealth no matter the cost, all the while war cries are heard from France, as Napoleon sets forth a violent master plan to become emperor of the world. As institutions are challenged and toppled in unprecedented fashion, ripples of change ricochet through our characters’ lives as they are left to reckon with the future and a world they must rebuild from the ashes of war. Over thirty years ago, Ken Follett published his most popular novel,  The Pillars of the Earth . Now, with this electrifying addition to the Kingsbridge series we are plunged into the battlefield between compassion and greed, love and hate, progress and tradition. It is through each character that we are given a new perspective to the seismic shifts that shook the world in nineteenth-century Europe.